The Visegrad countries as an example to emulate? German expectations within the Eastern partnership - Kriz, Zdeněk; Urbanovska, Jana; Brajercikova, Stanislava (2019)
Abstract: The Central European countries have been members of the European Union (EU) since 2004. During the process of their transformation towards democracy and market economy, the four Visegrad countries (V4) -the Czech Republic, Hungary, Poland, and Slovakia- were strongly supported by Western European EU members, particularly Germany, which was especially interested in the EU Eastern enlargement. Later on, Germany undertook a similar approach in assisting the transformation towards democracy and market economy in the countries included in the Eastern Partnership (EaP) initiative, forming the Eastern dimension of the European Neighborhood Policy. Unlike in the past, however, current Berlin policy-makers are no longer willing to support an Eastern enlargement of the EU. Nevertheless, Germany expects the V4 to intensively engage with the EaP countries (i.e. Armenia, Azerbaijan, Belarus, Georgia, Moldova, and Ukraine) and to share their experiences from the political and economic transforma